Plants Pre-Infested With Viruliferous MED/Q Cryptic Species Promotes Subsequent Bemisia tabaci Infestation - Shi, Xiaobin; Chen, Gong; Pan, Huipeng; Xie, Wen; Wu, Qingjun; Wang, Shaoli; Liu, Yong; Zhou, Xuguo; Zhang, Youjun (Frontiers in Microbiology, 2018)
The sweet potato whitefly, Bemisia tabaci, is one of the most invasive insect pests worldwide. The two most destructive whitefly cryptic species are MEAM1/B and MED/Q. Given that MED/Q has replaced MEAM1/B in China and the invasion of MED/Q has coincided with the outbreak of tomato yellow leaf curl virus (TYLCV), we hypothesize that pre-infestation with viruliferous B. tabaci will affect the subsequent host preferences. To test this hypothesis, we 1) conducted bioassays to compare the host preference of viruliferous and nonviruliferous MEAM1/B and MED/Q, respectively, on plants pre-infested with viruliferous and nonviruliferous MEAM1/B and MED/Q; 2) profiled plant volatiles using GC-MS; and 3) functionally characterized chemical cues could potentially modulate B. tabaci-TYLCV-tomato interactions, including ρ-cymene, thujene and neophytadiene, using a Y-tube olfactometer. As a result, plants pre-infested with MEAM1/B whiteflies carrying TYLCV or not, did not attract more or less B or Q whiteflies. Plants pre-infested with non-viruliferous MED/Q resisted MEAM1/B but did not affect MED/Q. However, plants pre-infested with viruliferous MED/Q attracted more whiteflies. Feeding of viruliferous MED/Q reduced the production of ρ-cymene, and induced thujene and neophytadiene. Functionally analyses of these plant volatiles show that ρ-cymene deters while neophytadiene recruits whiteflies. These combined results suggest that pre-infestation with viruliferous MED/Q promotes the subsequent whitefly infestation and induces plant volatile neophytadiene which recruits whiteflies.